Mental health: current trends in pharmacy and new concepts - N. A. Bilousova; A. V. Kabachna (Zaporozhye State Medical University, 2023)
The implementation of the National Mental Health Gap Action Program (mhGAP), which aims to broaden the management of patients with mental disorders in primary care, should involve not only primary care physicians but also pharmacists. Pharmacists play a crucial role by providing medications within the expanded Medical Guarantee Program for drug reimbursement in outpatient treatment of mental and behavioral disorders. Additionally, they offer pharmaceutical care for patients dealing with stress disorders and insomnia, adhering to the Good Pharmacy Practice (GPP) standards. The aim of the work is the study of national information, scientific databases, and scientometric databases of Scopus, Web of Science, PubMed, Cochrane Library in order to identify, generalize, and systematize the source based on providing pharmaceutical care in the field of mental health care of patients and predicting the future vector of research on the specified topic. Materials and methods. General scientific methods such as analysis, synthesis, comparison, and data generalization from domestic information and scientific databases were employed in this study. To search for scientific publications, the VOS viewer visualization program, the PubMed search engine, and the Cochrane Library were used. The keywords "mental health" and "pharmacy" were used for the search within the scientometric databases of Scopus and Web of Science. Results. The analysis of the main strategies for the development of pharmaceutical care for mental health care in pharmaceutical practice was carried out. The most researched clusters of mental health care were singled out. Modern trends in the development of pharmaceutical care for mental health care were summarized. Conclusions. The initiative for enhancing mental health care for the country's population hinges on the principles of a novel, sustainable, patient-centered pharmacy model. This approach necessitates the realization of an expanded role for pharmacists, aligning with the standards outlined in Good Pharmacy Practice.